Breastfeeding moderates the relationship between fat mass and obesity‐associated gene rs9939609 and body mass index among adolescents - Sofia H. Kanders; Kent W. Nilsson; Cecilia Åslund (Wiley, 2022)
Abstract Objective Breastfeeding, which is important for early growth, is a possible moderator of genetic influence, such as the effect of the fat mass and obesity‐associated gene (FTO) on body mass index (BMI). The aim of this study was to assess the moderating effect of breastfeeding duration on the relationship between FTO rs9939609 and BMI in a Caucasian sample. Methods Adolescents born in 1997 and in 1999, who were living in the Swedish county Västmanland in 2012, were invited to participate in the Survey of Adolescent Life in Västmanland. The adolescents and their parents completed self‐reported questionnaires in 2012, 2015, and 2018. Genotyping of rs9939609 T > A polymorphism was conducted from saliva DNA samples. Interaction effects of parental reported breastfeeding duration in months, including regions of significance, on the relationship between rs9939609 and BMI plus overweight were assessed. Results Considering physical activity levels, parental reported breastfeeding duration was a moderator of the relationship between rs9939609 and BMI for the younger (regions of significance = <1.6 and >28.1 months) and older adolescents (region of significance = >19.9 months), but not for the young adults. Plots of the association between breastfeeding duration and BMI showed higher BMI for AA with short breastfeeding, but lower BMI with longer breastfeeding than AT and TT. Longer breastfeeding lowered the odds for overweight among the younger adolescents, especially among AA individuals. Conclusion Rs9939609 AA individuals were more susceptible than AT and TT individuals to both short and long breastfeeding durations, which is consistent with the differential susceptibility hypothesis. FTO rs9939609 AA might be a plasticity variant with differential susceptibility to environmental influences. Breastfeeding duration may be one of many factors that affect the relationship between rs9939609 and BMI.